Interaction Patterns of Teachers and Students in Online Learning Subjects Al-Quran Hadith - Hidayatur Rohmah; Shofi Eviyanti (APPLICATION: Applied science in Learning Research, 2022)
The purpose of this study was to determine the interaction patterrns of teachers and students in online learning of al-quran hadist subjects MA Assulaimaniyah Mojolegi Mojoagung. Qualitative Research method with theoretical analysis approach using interview, observation and documentation techniques,the result of this research is to know the interaction pattern teachers and student in online learning and knowing the inhibiting factors and supporting factors for online learning while the inhibiting factor is the constraint of communication tools, games and helping parents. And the supporting factors for online learning are data packages from the government, teacher motivation.